Pengaruh Psikologis Konsumen Terhadap Keputusan Pembelian Produk Smartphone Merek Vivo (Studi Kasus Pada Masyarakat Dusun II Desa Tanjung Mulia Kecamatan Tanjung Morawa) - Dewi Fatmah; Rukmini Rukmini (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2022)
This study uses descriptive data analysis methods to describe or analyze research results but are not used in making broad conclusions, and this study also uses quantitative methods, namely the method used to show data in the form of numbers. Purchase of Vivo Brand Smartphone Products from the Community of Hamlet II, Tanjung Mulia Village, Tanjung Morawa District. Data collection techniques using interviews, questionnaires, observations. The results of consumer psychology research have a positive and significant effect on purchasing decisions which are indicated by the value of tcount> ttable (5.169>1.98447) and significant at 0.000 <0.05. The coefficient of determination (R square) is 0.214, which means 21.4% of the purchasing decision variables. can be explained by the independent variable Consumer Psychology, while the remaining 78.6%. Keywords: Psychological, Consumer, Vivo Smartphone